The Influence of Interest and Talent Guidance through Religious Activities on The Development of Soft Skill Potential among Santri - Gema Akbar Putra Pamungkas; Dhikrul Hakim; Siti Asiah (Indonesian Publication Center, 2026)
This study aims to examine the implementation of interest and talent guidance through religious activities, the development of soft skill potential among santri, and the influence of such guidance on that development at the Bani Umar Putra Dormitory of the Darul Ulum Islamic Boarding School in Jombang. The study employs a quantitative approach using purposive sampling, supplemented by observation, interview, and documentation data to enrich the interpretation of statistical results. The study population consisted of 140 santri, with a sample of 35 first-year junior high school level (SLTP) students. Primary data collection was conducted using a Likert-scale questionnaire. Data analysis involved validity and reliability tests, percentage analysis, normality tests, and multiple linear regression using SPSS software. The results indicate that the santri's talent falls into the